2015
DOI: 10.3906/bot-1402-69
|View full text |Cite
|
Sign up to set email alerts
|

The phytoplankton functional group concept provides a reliable basis forecological status estimation in the Çaygören Reservoir (Turkey)

Abstract: Padisak et al. (2009) modified the original functional classification system by reviewing numerous studies dealing with the FG concept and described typical misplacements by authors. It then was applied in numerous studies (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…This situation could be considered as a sign of an eutrophication process. The codon T was also reported from Batman dam reservoir (Varol, 2019), Çaygören Reservoir (Çelik and Sevindik, 2015), and Lake Garda (Salmaso, 2002) Codon C (C. atomus and C. meneghiniana), Codon D (U. acus) and Codon P (F. capucina) functional groups are diatoms which were detected in Lake İznik at different periods. Di Maggio et al (2016) reported three annual peaks for diatoms: the codon P is in summer, the codon C is in early winter, and the codon D is between late winter and early spring.…”
Section: Pfgs and Their Ecological Preferencesmentioning
confidence: 69%
See 1 more Smart Citation
“…This situation could be considered as a sign of an eutrophication process. The codon T was also reported from Batman dam reservoir (Varol, 2019), Çaygören Reservoir (Çelik and Sevindik, 2015), and Lake Garda (Salmaso, 2002) Codon C (C. atomus and C. meneghiniana), Codon D (U. acus) and Codon P (F. capucina) functional groups are diatoms which were detected in Lake İznik at different periods. Di Maggio et al (2016) reported three annual peaks for diatoms: the codon P is in summer, the codon C is in early winter, and the codon D is between late winter and early spring.…”
Section: Pfgs and Their Ecological Preferencesmentioning
confidence: 69%
“…Few studies had also been conducted to use PFGs in determination of the water quality of Turkish reservoirs and lakes in recent years (Soylu and Gönülol, 2010;Çelekli and Öztürk, 2014;Demir et al, 2014;Maraşlıoğlu and Gönülol, 2014;Çelik and Sevindik, 2015;Sevindik et al, 2017;Varol, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Elser & Urabe (1999) noted that increased biomass of D. galeata when nitrogen concentrations increased in Lake Biwa, Japan. The phytoplankton of the Çaygören Reservoir is dominated by the nitrogen fixing Cyanobacteria during warm seasons (Çelik & Sevindik, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, phytoplankton functional groups estimated reliable water quality states between hypertrophic and oligotrophic conditions in a reservoir of Turkey (Çelik and Sevindik, 2015), indicated eutrophication due to human impacts along the river Loire in France (Abonyi et al, 2012), and allowed an ecological assessment of French Atlantic lakes (Cellamare et al, 2012).…”
Section: Reaction Of Phytoplankton Functional Groups To Ecological Stmentioning
confidence: 99%